Effects of Sputtered InxSy Buffer on CIGS with RbF Post-Deposition Treatment. (10th May 2021) - Witte, Wolfram; Hempel, Wolfram; Paetel, Stefan; Menner, Richard; Hariskos, Dimitrios
Abstract : Indium sulfide (Inx Sy ) is an attractive candidate to be used as a buffer layer for Cu(In, Ga)Se2 (CIGS) thin-film solar cells and modules. Inx Sy sputtering would be the preferred deposition method of choice as it allows for much higher growth rates compared to all other current deposition methods. A key feature of CIGS absorber processing, established during the last years, is the use of a post-deposition treatment (PDT) with alkali compounds. In this work, we apply rf-magnetron sputtered Inx Sy buffers from ceramic targets, optionally doped with NaF, on industrially relevant CIGS absorbers with or without RbF-PDT prepared in an in-line coater. We analyze the influence of wet chemical treatments of the CIGS surface after RbF-PDT and alkali accumulation at the Inx Sy /CIGS interface on the solar cell performance. Good efficiencies could be achieved with sputtered Inx Sy on CIGS with RbF in an all-dry process. An Inx Sy deposition temperature around 200 °C and/or a post-annealing step of the complete cell in air emerged as a key feature for decent efficiencies. This is also due for sputtering from a NaF-doped In2 S3 target. Our best cell with sputtered Inx Sy on CIGS with RbF-PDT shows an efficiency of 18.0% with a high open-circuit voltage of 701 mV.